Peridotite xenoliths in Colorado-Wyoming kimberlites - Kirkley, Melissa Bradford, author; McCallum, M. E., advisor (Colorado State University. Libraries, 1980)
Mantle peridotite xenoliths in Colorado-Wyoming kimberlites include abundant dunites, garnet and/or spinel harzburgites, lherzolites, clinopyroxenites and websterites. Garnet and/or spinel wehrlites, olivine websterites and orthopyroxenites are less common. Coarse equant and tabular, transitional-porphyroclastic, porphyroclastic, mosaicporphyroclastic and granuloblastic textural types are recognized in both altered and unaltered xenoliths. The term porphyroblastic is introduced to describe textures observed in some olivine-free pyroxenite xenoliths. Special textural features such as exsolution phenomena and garnet rims around spinel are also present. Six lithologic groups are defined on the basis of mineral and whole rock chemistry. Minerals of Group I garnet peridotites are rich in Cr2O3, relatively high in MgO, and generally poor in Al2O3 and FeO, although clinopyroxenes of porphyroclastic xenoliths are slightly enriched in FeO. Minerals of Group II and III xenoliths, spinel peridotites of Sloan-Nix-Moen and Iron Mountain kimberlites respectively, have relatively high levels of Cr2O3 and MgO and low FeO, TiO2, Al2O1 and Na2O. Olivine-free, garnet and/or spinel pyroxenites comprise Group IV and their minerals are poor in Cr2O3 and generally high in FeO, TiO2 and Al2O3. Group V, the "Websterite Group," consists of a variety of rock types. Mineral compositions of Group V xenoliths are generally intermediate between those of Groups I and IV. Dunites, which comprise Group VI, have a bimodal distribution exhibited by forsterite compositions. Whole rock chemistry calculations determined on fresh nodules of Groups I, II, IV and Vindicate that Group I and II xenoliths are most depleted in FeO, TiO2, CaO and Na2O whereas nodules of Group IV are richest in these oxides. Group V xenolith compositions are intermediate between and overlap with those of Group I and IV. Estimates of temperatures and pressures of equilibration made on fresh xenoliths suggest that Group I nodules formed above 1100°C at depths in excess of 150 km (50 kb). Group I xenoliths with porphyroclastic textures exhibit slightly higher temperatures and pressures than other nodules. Most xenoliths of Groups II, IV and V equilibrated at temperatures below 900°C and at depths of less than 100 km (30 kb). Spinel coexisting with garnet persists to depths of approximately 80 km (25 kb). Texture and chemistry correlations reported from some garnet peridotite suites from African kimberlites are not observed in Colorado-Wyoming kimberlites. Chemistry of Group II and III spinel peridotites indicates these nodules may have undergone partial melting. Group IV garnet ± spinel pyroxenites may represent crystallized partial melts or cumulates from partial melts. Spinel in some peridotites of Group V appears to have reacted with orthopyroxene to form garnet rims. The two varieties of dunites, Group VI, may represent cumulates relatively rich in FeO, and residual dunites depleted in FeO.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Kimberlite -- Colorado; Kimberlite -- Wyoming; Colorado; Wyoming